Detection of Vibrio parahaemolyticus infection-resistant biomarkers in tiger grouper Epinephelus fuscoguttatus (Forsskǻl) using quantitative real-time PCR method - Ibrahim, Nur Liyana (2019)
Grouper species which includes Epinephelus fuscoguttatus also known as tiger grouper is one of the valuable species with great economic value in Southeast Asian countries. Various infectious diseases occur in grouper aquaculture and often create severe problems leading to economic losses. Causative agents of vibriosis in aquaculture include Vibrio parahaemolyticus. Vibrio parahaemolyticus is a major foodborne pathogen and classified as a Gram-negative halophilic bacterium which commonly inhabits estuarine and marine environments and causes worldwide health problems on consumption. Therapeutic options with antibiotics and vaccines have disadvantages such as resistance and contamination from overuse. For centuries farmers have been aware of specific phenotypic attributes in plants and animals that provided a production advantage of one species over another. The advances in technology have permitted researchers to examine these features at the genetic and molecular levels. Selective breeding is a viable option to improve health of fish in culture. Feasible and rapid methods for identification of relevant biomarkers in groupers are factors that aid in management of its produce. Real time qPCR-based methods are convenient, easy to screen for epidemiological, genetic studies and applicable to routine high-throughput detection of large numbers of samples and can be used for quantitative gene expression of biomarkers in grouper organs and tissues. The purpose of this study is to confirm usefulness of previously identified biomarkers in selection of fish with disease resistance. Herein the potential biomarkers, the alpha-2-Macroglobulin (α2M), Parvalbumin Beta-2 Subunit 1 (PVALB) and Nattetin genes were selected. Primers were designed using Primer-BLAST from the NCBI website and synthesized by a local company. β-actin (ACTB), acted as the reference gene. Experimental infections of grouper with V. parahaemolyticus were conducted to assess expression levels of these genes in infected fish compared to controls. Healthy juveniles’ grouper fish infected with V. parahaemolyticus were monitored for skin lesions in tissues and samples collected after 2 weeks. Vibrio parahaemolyticus infected grouper displayed significantly increased expression of alpha-2-Macroglobulin (α2M), Parvalbumin Beta-2 Subunit 1 (PVALB), and Nattectin in blood, liver and spleen compared to before infection. Infection susceptible fish was based on the development of skin lesion more than five millimeter (>5mm) in diameter while none was observed on infection resistant fish. When infection-resistant fish was compared to fish infection-susceptible for these three genes Nattectin, PVALB, and α2M, q-PCR analysis showed two-fold, two-fold, and four-fold significant under-expressions in the liver tissue, respectively. Similarly, significantly down-regulation (p<0.05) was observed for Nattectin and PVALB by three-fold and two-fold, except for α2M with no significant difference in expression in spleen sample. Again, in blood samples Nattectin was significantly decreased by four-fold, PVALB by two-fold, and α2M by three-fold in infection-resistant samples. However, these results did not replicate data obtained from an earlier study which used proteomic method. Nevertheless, this study demonstrated that Nattectin, PVALB, and α2M were over-expressed in infection-susceptible fish providing evidence on the involvement of these gene during V. parahaemolyticus infection. These data will provide the foundation for use of biomarkers in identification of disease resistant groupers and selective breeding.